Corporate convenience store development effects in small towns: Convenience culture during economic and digital storms. (February 2019) - Wrigley, Neil; Wood, Steve; Lambiri, Dionysia; Lowe, Michelle
The impact of the global economic crisis, together with the 'digital' storm of unrelenting growth in online retail and its complex substitution and modification effects, had significant implications for UK town centres and high streets. Dramatically increased vacancy rates within town centres have focused policy debate on the drivers of town centres' vitality and viability in the context of profound technological and consumer culture shifts. As consumers turned away from 'big basket' one-stop weekly shops at large out-of-centre stores and began shopping 'little and often' using a fragmented range of alternatives, the convenience store sector, significantly altered by corporate entry, grew rapidly. However, there is surprisingly little empirical evidence on the impacts of these new-generation corporate convenience stores on town centres and communities. This paper helps fill that gap by reporting the findings of a study of five small towns in southern England. Drawing on evidence from surveys of over 1500 consumers and 200 traders, we show that despite their modest size, these stores have rapidly assumed significant and little-documented trip generation and 'anchor' roles essential to the sustainability of the centres. Moreover, they have facilitated trends towards 'relocalization' of food shopping, reduction in car dependency and higher than expected levels of linked trips. In this paper, we draw out the significance of those findings and position them within wider conceptual and policy debates. We also stress the spatially and temporally contingent nature of the findings within a dynamic technological and regulatory context.